More deadly than war : the hidden history of the Spanish flu and the First World War - Davis, Kenneth C. (Henry Holt and Company, 2018)
Explores one of the most deadly outbreaks of disease in history during the time of World War I when the Spanish Flu affected Europe and the United States.